Intramuscular DNA vaccine provides protection in non-human primate and mouse models of SARS-CoV-2 - Sood, Subeena; Gary, Ebony N.; Matar, Majed; Kim, Jessica; Hojecki, Casey E.; Warner, Bryce; Vendramelli, Robert; Truong, Thang; Smith, Alanna; Rice, Jennifer; Sparks, Jeff; DeSalvo, Michael; et al. (Frontiers in Immunology, 2025)
Nucleic acid vaccine approaches have proven successful in the context of the SARS-CoV-2 pandemic, however challenges with delivery remain. Here we describe PlaCCine, a DNA-based vaccine platform that utilizes a device- and vector-free chemical delivery system. This system includes a DNA plasmid encoding the target antigen and generates robust immune responses, offering significant protection against live viral challenges in both non-human primates and mice. We designed spike plasmid immunogens representing early SARS-CoV-2 strains and found that parental spike PlaCCine vaccination induced SARS-CoV-2 specific cellular and humoral responses in non-human primates and supported significant viral control following challenge. To evaluate immunogenicity and protective efficacy against emerging variants, we further advanced the platform to incorporate the SARS-CoV-2 XBB1.5 variant and observed robust, dose-dependent cellular and humoral responses in mice. When mice were immunized and intranasally challenged with 1×105 TCID50 of SARS-CoV-2 XBB1.5 virus, all immunized animals survived the challenge and displayed undetectable lung viral loads. Together these data demonstrate the efficacy of the PlaCCine platform for the delivery of vaccine antigens and support the continued translation of this platform for infectious diseases.